2022
DOI: 10.1093/bjd/ljac001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Oleogel-S10 (birch triterpenes) for epidermolysis bullosa: results from the phase III randomized double-blind phase of the EASE study

Abstract: Background  Epidermolysis bullosa (EB) is a heterogeneous group of rare, difficult-to-treat, inherited multisystem diseases affecting epithelial integrity. Patients with EB are affected by mechanical fragility of epithelial surfaces including the skin and, as a result, extensive recurrent blistering is a characteristic of the condition. Chronic wounds predispose patients with EB to the development of squamous cell carcinoma, which is a major cause of premature death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…Research has revealed that the application of topical birch triterpenes enhances wound healing within 45 days. Importantly, the incidence of AE, including infections, was found to be similar to that observed with control gel treatment (Kern et al 2023 ). The FDA granted birch triterpenes orphan drug, fast track, and priority review designations.…”
Section: Dermatologysupporting
confidence: 69%
“…Research has revealed that the application of topical birch triterpenes enhances wound healing within 45 days. Importantly, the incidence of AE, including infections, was found to be similar to that observed with control gel treatment (Kern et al 2023 ). The FDA granted birch triterpenes orphan drug, fast track, and priority review designations.…”
Section: Dermatologysupporting
confidence: 69%
“…For example, results of a recent phase 3 trial in patients with severe forms of EB found that the topical gel Oleogel-S10 (birch bark extract, also referred to as birch triterpenes) demonstrated accelerated wound healing by achieving complete target wound closure in 41.3% of target wounds compared to 28.9% with vehicle control gel ( P = .013) within 45 days. 16 This accelerated wound healing with Oleogel-S10 resulted in a reduction in total body wound burden. 16 , 17 On the basis of these results, Oleogel-S10 (birch bark extract) has now been approved for treatment of partial thickness wounds associated with JEB and DEB in the EU and UK.…”
Section: Discussionmentioning
confidence: 99%
“… 16 This accelerated wound healing with Oleogel-S10 resulted in a reduction in total body wound burden. 16 , 17 On the basis of these results, Oleogel-S10 (birch bark extract) has now been approved for treatment of partial thickness wounds associated with JEB and DEB in the EU and UK. Another recent publication reporting the phase 3 trial evaluating the redosable topical gene therapy beremagene geperpavec, in patients with DEB reported complete wound healing occurred in 67% of the wounds exposed to beremagene geperpavec as compared with 22% of those exposed to placebo ( P = .002).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the rst two treatments for EB skin wounds have been recently approved by regulatory agencies. The rst one, Oleogel-S10, is a gel containing triterpenes extracted from birch bark that proved effective and safe in accelerating healing of EB wounds and reducing pain [33]. Oleogel-S10 has been approved by the European Medicine Agency (EMA) and the Food and Drug Administration (FDA) for use in DEB and JEB patients aged > 6 months.…”
Section: Discussionmentioning
confidence: 99%